HEAD LOSSES ACROSS MICROIRRIGATION LATERALS - CARDOSO, GABRIEL GRECO DE GUIMARÃES; FRIZZONE, JOSÉ ANTÔNIO (Revista Brasileira de Engenharia de Biossistemas, 2007)
Microirrigation lateral design procedure needs to evaluate accurately both the pipe headlosses and the local losses that are due to the protrusion of emitter barbs into the flow.These local losses, in fact (in relation to the high number of emitters located along theline) can become significant compared to the overall energy loss. On this paper, the resultsof an experimental study on the pipe head losses, friction factor and head local losses forsmall-diameter polyetilene pipes are reported. The experiment was carried out using arange of Reynolds number between 6000 to 72000, obtained by varying discharge at 202 oC water temperature. Five internal diameter pipes were used: 10,0, 13,0, 16,3, 17,4and 19,7 mm; and four connector models with a protrusion areas of 19,70, 23,59, 26,50 e31,63 mm2. According to the results analysis and experimental conditions the frictionfactor (f) of the Darcy-Weisbach equation can be estimated with c = 0,300 and m = 0,25.The Blasius equation (c = 0,316 and m = 0,25) gives a overestimative of f (5,1%). Toderive an estimating procedure of K, the geometry of the connection between the emitterand the pipe was characterized by the obstruction index IO, which is dependent on theratio (r) between the pipe cross-section area corresponding to the section in which theemitter is located, and the pipe cross-section area. A power relationship was then fitted tothe experimental IO, K data pairs. The selection form of the relationship is consistent withthe physical phenomenon since it estimates K = 0 for r = 1 (no obstruction into the pipe).For 6000<R<72000 the relationship was K = 1,23 (IO)0,51 with R2 = 0,9556 and standardfitted error equal to 0,04245. The differences between K observed values and the calculatedones are normally distributed.